Role of information and communication technologies on the war against terrorism and on the development of tourism: Evidence from a panel of 28 countries. (August 2020) - Choudhary, Sheraz Ahmad; Khan, Muhammad Azhar; Sheikh, Abdullah Zafar; Jabor, Mohd Khata; Nordin, Mohd Safarin bin; Nassani, Abdelmohsen A.; Alotaibi, Saad M.; Abro, Muhammad Moinuddin Qazi; Vo, Xuan Vinh; Zaman, Khalid
Abstract: This study aims to examine the dynamic relationships among information and communication technologies (ICTs), international tourism, and terrorism in 28 countries from 1998 to 2016. Three weighted indices were constructed to gather the following factors: i) "war against terrorism" by military factors, ii) ICTs by different communication technologies, and iii) tourism demand by tourism factors. Results confirmed that the potential determinants of the war against terrorism include computer and communication services, secure Internet servers, per capita income, and trade openness. The key factors of ICT development are armed forces personnel, arms imports, military expenditures, per capita income, and trade openness, which can be effectively utilized for the war on terrorism across countries. Per capita income, trade, foreign direct investment inflows, and military expenditures substantially increased inbound tourism, whereas tourism demand increased computer and communication services, Internet users, and trade openness. Results also showed that armed forces personnel, arms imports, and growth-specific factors substantially increased tourism receipts, whereas high military expenditures decreased tourism income. These findings offer useful policy implications. One key conclusion drawn from this study is that ICTs play a potentially vital role in supporting the war against terrorism and the development of tourism across countries. Highlights: To examine the relationship between ICTs, terrorism, and tourism in a panel of 28 countries. Global terrorism index is used to select the countries between 5 (moderate) and 10 (high terrorism incidence). Panel FMOLS estimator is used for robust inferences. Principal component matrix is used to construct war against terrorism, ICTs, and tourism index. The results confirmed that ICTs largely supported war against terrorism and tourism across countries.